Acantorna—a new genus of Hymedesmiidae (Porifera, Demospongiae, Poecilosclerida) from the western Aleutian Islands of Alaska with description of Acantorna tahoma n. sp. - Lehnert, Helmut; Stone, Robert P. (Zootaxa, 2020)
A sponge collected along the Aleutian Islands of Alaska revealed an unusual combination of characters including ectosomal acantho - tornotes never before observed. Assignment to Poecilosclerida is without any doubt due to the presence of chelae but assignment to family is more problematic because 1) there is no family of Poecilosclerida (or any other demosponge) with ectosomal acantho-tornotes, and 2) the combination of occurring spicules and their arrangement does not conform completely to any Poecilosclerid family. Thus family assignment is only possible by amending the concept of an existing poecilosclerid family and allow for spined as well as smooth tornotes and a confusedly plumose choanosomal arrangement of megascleres. We suggest assignment to Hymedesmiidae as this requires relatively slight changes compared to other Poecilosclerid families. We suggest the erection of Acantorna n. gen. to accommodate Acantorna tahoma n. sp. The new genus and species differ from all other Hymedesmiid genera in the possession of the characters necessary for the suggested amendment. Additional differences to each Hymedesmiid genus are added.